Biofuels and grain prices: Impacts and policy responses - Rosegrant, Mark W. (International Food Policy Research Institute, 2008)
Recent dramatic increases in food prices are having severe consequences for poor countries and poor people. The Food and Agriculture Organization of the United Nations (FAO) reports that food prices rose by nearly 40 percent in 2007 and made further large jumps in early 2008. Nearly all agricultural commodities-including rice, maize, wheat, meat, dairy products, soybeans, palm oil, and cassava-are affected. In response to the price hikes, food riots have occurred in many developing countries, including Burkina Faso, Cameroon, C?te d'Ivoire, Egypt, Haiti, Indonesia, Senegal, and Somalia. According to the FAO, 37 countries are now facing food crises.